2005
DOI: 10.1021/jf052000u
|View full text |Cite
|
Sign up to set email alerts
|

Natural Compounds Derived from Foods Modulate Nitric Oxide Production and Oxidative Status in Epithelial Lung Cells

Abstract: The effects of natural antioxidants on nitric oxide (NO) modulation and oxidative status were determined in rat epithelial lung cells (L-2). Cells were stimulated with cytokines and treated with one of the following: resveratrol, soybean saponin group B (SSB), quercetin, genistein, olive leaf polyphenol concentrate (OLPC), or N-acetyl-L-cystein (NAC). NAC had no effect on NO levels, whereas resveratrol and OLPC were found to be effective in reducing nitrite levels, modifying iNOS mRNA, and decreasing free radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…Olive leaf extract. Olive leaf extract was prepared from olive leaves as described by Zaslaver et al 16 Briefly, the leaves were randomly picked from the Barnea cultivar in the Jezreel Valley region of Israel and immediately freeze dried on dry ice. After being thoroughly rinsed with sterile distilled water to remove dust, insecticides, and contaminating material, the olive leaves were ground and Soxhlet extracted with hexane for 3 h followed by 80% aqueous ethanol for 6 h. The alcoholic extract was concentrated under reduced pressure at 25°C, and the powder was encapsulated.…”
Section: Interventionmentioning
confidence: 99%
“…Olive leaf extract. Olive leaf extract was prepared from olive leaves as described by Zaslaver et al 16 Briefly, the leaves were randomly picked from the Barnea cultivar in the Jezreel Valley region of Israel and immediately freeze dried on dry ice. After being thoroughly rinsed with sterile distilled water to remove dust, insecticides, and contaminating material, the olive leaves were ground and Soxhlet extracted with hexane for 3 h followed by 80% aqueous ethanol for 6 h. The alcoholic extract was concentrated under reduced pressure at 25°C, and the powder was encapsulated.…”
Section: Interventionmentioning
confidence: 99%
“…Excess inflammatory mediators (NO and PGE 2 ) and pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6) produced by activated macrophages induce inflammatory process and act synergistically with other inflammatory mediators [2,4,5]. Natural compounds able to inhibit the production of inflammatory mediators or pro-inflammatory cytokines may be attractive as anti-inflammatory agents and, for this reason, the inhibitory effects of phytochemicals on the production of inflammatory mediators or pro-inflammatory cytokines have been intensively studied to develop therapeutic agents for preventing inflammatory diseases [8,11,21]. Recent studies have shown that in vivo or in vitro treatments of natural compounds are effective in reducing inflammation by the suppression of pro-inflammatory cytokines, which may treat inflammation-related diseases, including atherosclerosis, cancer, and inflammatory arthritis [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had verified their effects on regulating cholesterol levels and hypertension, two risk factors commonly associated with heart disease and Alzheimer's disease.the Polyphenols could prevent damage caused by oxidation or neural death in cell cultures [28].…”
Section: D Di Is Sc Cu Us Ss Si Io On Nmentioning
confidence: 99%